Kepentingan Komunikasi Kepemimpinan Dalam Organisasi Awam Di Malaysia: Satu Analisis Konsep - Safei, Su'aidi; Raja Abd.Rahman, Raja Roslan; Mat Diah, Abu Bakar (2005)
Leadership communication skills in any field dominated by a leader will strengthen his/her ability to administer and manage the public organization in Malaysia. This will lead to successful inter relation between manager and subordinate, and vice-versa.